Large-scale preparation method for aluminum or aluminum alloy anti-frosting surface - ZHANG HAIFENG; LIU XIAOWEI; TUO YANJING; RONG WANTING (2019)
The invention discloses a large-scale preparation method for an aluminum or aluminum alloy anti-frosting surface. The preparation method includes the following steps: first, the aluminum or aluminum alloy is etched in HCl solution through a chemical corrosion method to obtain a rough surface with the micron structure, second, a nanometer-scale roughness structure on the rough surface is grown by adopting the method of hydrothermal synthesis in a boiling water bath to obtain a micro-nanometer composite binary rough surface, and finally a surface with super-hydrophobic property is obtained by the modification of a resin low-surface-energy substance. The preparation method has the advantages that the method is simple, the requirements for equipment are low, a traditional modified fluoride molecular layer is replaced with the resin, the durability of the super-hydrophobic surface is greatly improved, the production cost is reduced, and the super-hydrophobic surface prepared according to the method is characterize